The Basic Analytics of Access to Financial Services - Beck, Thorsten; de la Torre, Augusto (World Bank, Washington, DC, 2012)
Access to financial services, or rather the lack thereof, is often indiscriminately decried as a problem in many developing countries. The authors argue that the "problem of access" should rather be analyzed by identifying different demand and supply constraints. They use the concept of an access possibilities frontier, drawn for a given set of state variables, to distinguish between cases where a financial system settles below the constrained optimum, cases where this constrained optimum is too low, and-in credit services-cases where the observed outcome is excessively high. They distinguish between payment and savings services and fixed intermediation costs, on the one hand, and lending services and different sources of credit risk, on the other hand. The authors include both supply and demand side frictions that can lead to lower access. The analysis helps identify bankable and banked population, the binding constraint to close the gap between the two, and policies to prudently expand the bankable population. This new conceptual framework can inform the debate on adequate policies to expand access to financial services and can serve as the basis for an informed measurement of access.